Th Good governance in the light of contemporary political thought (Salam International Academic Journal, 2019)
Good governance is as important for developing countries is important for developed countries as well. Some organizations notice good governance from the financial side while other observe it from the political point of view. According to both of them, the fundamental elements in good governance are, reduction of domination, electing someone by votes, giving all the people (especially the poorest class) opportunity to take part in their decision making and plans. Providing fair opportunities to the citizens of the country using their abilities. Making good and proper legislation and law enforcement, equality of people with law, and fighting against financial, organizational and political corruption. And the main objective of economical development is continuous improvement of human lives. If the lives of humans do not change positively, then if a country may even have enough money and resources but is not a developed country in the reality. To create good government is not only the task of government but also include some other organizations. Some important of them are social communities and some private sectors. Good governance is not only dependant to public administration as well but companies, private sectors and social communities also need good governance. And finally it is stated that the core objective of good governance is continuous improvement of human lives.
Keywords: Good Governance; Political Thought; Democracy; Authoritarian Interaction; Law